La Violencia Económica: panorama de Derecho Comparado - Cabrillac, Rémy (Pontificia Universidad Católica del Perú, 2016)
This paper explains how the notion of economic duress is understood in different legal regimes of Civil Law and Common Law. This way, the author first addresses the concept of economic duress from a restrictive sense (as a defect of consent) and, later, develops the concept from a wider perspective (taking into account an objective economic imbalance).

El presente artículo explica cómo se entiende la noción de violencia económica en diversos ordenamientos jurídicos tanto del Civil Law como del Common Law. Así, el autor aborda primero el concepto de violencia económica en un sentido restringido (como vicio del consentimiento), y posteriormente lo desarrolla desde una perspectiva más amplia (tomando en cuenta un desequilibrio económico objetivo).
Economic Duress: overview of Comparative Law
Keywords: Defects Of Consent; Economic Duress; Undue Influence; Psychological Violence; Voidability; Nullity; Vicios del consentimiento; Violencia económica; Abuso de influencia; Violencia psicológica; Anulabilidad; Nulidad; https://purl.org/pe-repo/ocde/ford#5.05.00